Design and Optimization Analysis of a Through Shaft Inner Rotor Electric Bicycle Reducer Device - Xiong Junkai; Huang Xingyuan (Jixie chuandong)
Based on the analysis of the overall structure of the existing hub motor used for electric bicycles, aiming at the problems of instability and large noise when the inner rotor of the hub motor adopts the left and right half shaft structure, a hub motor structure of the through shaft inner rotor and reduction device is improved and designed. Based on the optimization design theory, the minimum total volume of the reduction device is taken as the objective function to optimize. Creo software is used to draw the optimized 3D model of the reducer, and finite element analysis is carried out by Ansys Workbench software to check the strength and stiffness of the structure. The results show that the new design overcomes the defects of the left and right half shaft in the electric bicycle hub motor, the volume of the reducer is reduced by 8.6% after optimization, and the structural design strength and stiffness meet the requirements, which verifies the rationality of the structure, and provides a new idea and theoretical basis for the electric bicycle hub motor structure design and optimization.